The Clinical, Laboratory, Etiological Profile and Outcome of Acute Necrotizing Encephalitis of Childhood (ANEC) in Tertiary Care Centre from Southern India - Gowda, Vykuntaraju K.; Channabasappa, Basavakumar; Shivappa, Sanjay K.; Veerappa, Basavaraja G.; Lakshmikantha, Keshavamurthy Mysore (Journal of Pediatric Neurology, 2023)
Acute necrotizing encephalitis of childhood (ANEC) is characterized by respiratory or gastrointestinal infection and high-grade fever accompanied by rapid alteration of consciousness and onset of seizures. Diagnosis is based on clinical presentation and characteristic neuroimaging features. The aim of this study was to report the etiological, clinical, and radiological findings and therapeutic outcomes of ANEC. This is a retrospective chart review of children aged 1 month to 18 years diagnosed with ANEC, from January 2017 to May 2022 at a tertiary care center in Bangalore, India. Of 36 patients, 17 were males, with age ranging from 10 months to 15 years. Major presenting complaints were altered sensorium in 36 (100%), fever in 33 (91.6%), and seizures in 27 (75%). The etiologies included dengue and chikungunya in 2 (5.5%) cases, Japanese encephalitis, influenza, and RAN binding protein 2 (RANBP2) in 1 (2.7%) case each, and unknown in 29 (80.5%) cases. Common findings of the magnetic resonance imaging (MRI) of the brain were abnormal signals in thalami in 20/20 (100%) and in brainstem in 11/20 (55%). Computed tomography (CT) of the brain done in all 16 cases showed thalamic hypodensities. All patients received empiric antibiotics, antivirals, and intravenous methylprednisolone. The modified Rankin scale showed excellent outcomes in 19/25 (76%), 3 were bedridden (8.3%), and 3 died (8.3%). ANEC is common in children under 5 years of age (76.7%). Altered sensorium, fever, and seizures were the main presenting symptoms. Genetic testing must be done in case of family history and recurrence. CT brain is also very useful in an emergency setup; MRI brain can be useful to suspect and prognosticate.
Keywords: ANEC; RAN binding protein 2 (RANBP2); thalamic hyperintensities; modified Rankin scale